An analysis of consultations with the crowd doctors at Glasgow Celtic football club, season 1999–2000. Issue 4 (1st August 2001) - Crawford, M; Donnelly, J; Gordon, J; MacCallum, R; MacDonald, I; McNeill, M; Mulhearn, N; Tilston, S; West, G
Abstract : Objective —To analyse all clinical presentations to the crowd doctors at Scotland's largest football stadium over the course of one complete season. Methods —A standard clinical record form was used to document all consultations with the crowd doctors including treatment and subsequent referrals. The relevance of alcohol consumption was assessed. Results —A total of 127 casualties were seen at 26 matches, a mean of 4.88 per match. Twenty casualties were transferred to hospital, including one successfully defibrillated after a cardiac arrest. Alcohol excess was a major contributing factor in 26 cases. Conclusions —The workload of the crowd doctors was very variable and diverse. The social problem of excessive alcohol consumption contributed considerably to the workload. The provision of medical facilities at football grounds means that attendance there is now one of the least adverse circumstances in which to have a cardiac arrest. The study confirmed previous impressions that more casualties are seen at high profile matches.